Relationship between institutional factors and FDI flows in developing countries: New evidence from dynamic panel estimation - Zühal Kurul; A. Yasemin Yalta (Economies, 2017)
In this paper, we revisit the relation between institutional factors and foreign direct investment (FDI) inflows in developing countries by employing a dynamic panel methodology, which enables us to deal with the persistency of FDI flows and endogeneity issues. We also contribute to the literature by using various measures of institutions to identify which aspects of institutional quality affect FDI in the developing world. Our empirical findings based on 113 developing countries over the period 2002-2012 show evidence that some institutional factors matter more than others in attracting more FDI flows. We also found that the financial crisis in 2008 and 2009 had a negative impact on FDI flows.
Keywords: F21; C23; D73; P48; 330; institutions; foreign direct investment (FDI) flows; dynamic panel estimation; developing countries